ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN KINERJA PENGELOLAAN LINGKUNGAN PERUSAHAAN-PERUSAHAAN DI INDONESIA - Ahmad Fadhil Mubarok; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2016)
This study aims to analyze the factors that affect to disclosure of the company's environmental management performance in Indonesia. Measurements for the disclosure of corporate environmental management performance using PROPER issued by the Ministry of Environment and Forestry of the Republic of Indonesia. Object in this study are companies included in industry mining, agro-industry and manufacturing, are listed in the Indonesia Stock Exchange and always conduct financial reporting and assessed its environmental management performance through proper in 2012-2014. The sample was selected using purposive sampling method and obtained 86 sample. Data used is secondary data, such as financial statements, ACGS, and PROPER. Analysis of the data used is descriptive statistics, the classic assumption test, and regression analysis. The results of this study showed that the research period, environmental visibility, organisational visibility, profitability, financial distress and corporate governance significantly affect to the disclosure of corporate environmental management performance.